2022
DOI: 10.1051/ro/2022058
|View full text |Cite
|
Sign up to set email alerts
|

Technology license sharing strategy for remanufacturing industries under a closed-loop supply chain management bonding

Abstract: Remanufacturing is getting attention nowadays due to increasing waste and corresponding emissions. One of the important factors of remanufacturing is the quality of the remanufactured products. The collection and distribution of used products require proper management. Based on this situation, this study discusses a hybrid closed-loop supply chain management in cooperation with a hybrid production system. The vendor comes up with the policy of sharing remanufacturing responsibility by sharing the technology li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…Researchers are always busy for developing diverse inventory and supply chain models through their research of different demand patterns. Mondal et al [5] and Mahapatra et al [6] extended this direction with flexibility of production and promotional effort to reduce the cost as minimum as possible. Garai and Sarkar [7] concentrated on the customize products, ordered by customers, through the reverse logistics but without having the idea of trade-credit or game strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers are always busy for developing diverse inventory and supply chain models through their research of different demand patterns. Mondal et al [5] and Mahapatra et al [6] extended this direction with flexibility of production and promotional effort to reduce the cost as minimum as possible. Garai and Sarkar [7] concentrated on the customize products, ordered by customers, through the reverse logistics but without having the idea of trade-credit or game strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Goodarzian et al [69] proposed a multi-objective mathematical programming model for dealing with the productiondistribution problem. In addition, Mondal et al [70] modeled green products' distribution. Furthermore, Choi et al [71] suggested an intelligent two-channel (online-offline) for determining the products' selling prices.…”
Section: Supply Chain Coordination Problemmentioning
confidence: 99%
“…According to the literature review, various models have been presented by several researchers, but none of them have considered the three main aspects of the Kano model in the design of the supply chain network [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71]. This study considers the problem of a supply chain network design based on the motivational needs of customers.…”
Section: Problem Definitionmentioning
confidence: 99%
“…Despite the signifcance of trade credit in emergency pandemic situations, no studies have considered the efects of the pandemic and trade credit fnancing simultaneously in the SC model. Conversely, several studies have considered the efects of the pandemic and trade credit fnancing independently ( [21][22][23][24][25][26][27] for trade credit and [28][29][30][31][32][33][34] for pandemic efects). Specifcally, Tiwari et al [21] analyzed a green SC model for fawed products with a trade credit policy.…”
Section: Supply Chain Model With Pandemic Efects and Tradementioning
confidence: 99%